UJI DIAGNOSTIK PEMERIKSAAN C-REAKTIF PROTEIN (CRP) PADA NEONATUS TERSANGKA SEPSIS YANG DIRAWAT DI INSTALASI NEONATUS RSUD ARIFIN ACHMAD PROVINSI RIAU - Rum Affida Rasfa; Nazardi Oyong; Fatmawati " (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2015)
Neonatal sepsis is a collection of clinical symptoms and laboratory associated with infection due to the invasion of microorganisms during the first 28 days of a child's life time. The certain diagnosis of neonatal sepsis is the isolation of bacteria from blood or body fluids. However, this method takes at least 72 hours. Therefore, It is necessary an investigation with a relatively short time. One of methods is C-Reactive Protein (CRP) examination. Even though CRP examination has been done in many of diagnosis of sepsis,however this examination also has some limitations. This research designusing a diagnostic test with retrospective approach. The sampling technique is performed by consecutive sampling method and amount of sample is 313 people. The results showed that the characteristics of the neonatal sepsis suspect in accordance with age is early neonatal (0-6 h), which amount to 235 (75%), and majority is male by 182 (58%). The most risk factor for gestational age <37 weeks is 133 samples with a median value is 11.4 mg / dl. Late Onset Neonatal Sepsis (LONS) is the highest classification of sepsis group at 93 (82%) with a median value is 192 mg/dl. The diagnostic value of CRP examination are sensitivity 65.7%, specificity 79.3%, positive predictive value 64.6%, negative predictive value 80.2%, positive contingency ratio 3.25, negative contingency ratio 0.43 and accuracy of 74.4%. As the result, we obtain cut off the recommended point is ≥10,2 mg / dl.Keywords : sepsis, C-Reactive Protein (CRP), LONS